Investigation of the formation and intracellular stability of purine.(purine/pyrimidine) triplexes. - Debin, A (1997)
In a previous work we showed that a short triple helix-forming oligonucleotide (TFO) targeted to the murine c-pim-1 proto-oncogene promoter gives a very stable triple helix under physiological conditions in vitro . Moreover, this triplex was stable inside cells when preformed in vitro . However, we failed to detect triplex formation for this sequence inside cells in DMS footprinting studies. In the present work, in order to determine whether our previous in vivo results are limited to this particular short triplex or can be generalized to other purine.(purine/pyrimidine) triplexes, we have tested three other DNA targets already described in the literature. All these purine.(purine/pyrimidine) triplexes are specific and stable at high temperature in vitro . In vivo studies have shown that the preformed triplexes are stable inside cells for at least 3 days. This clearly demonstrates that intracellular conditions are favourable for the existence of purine. (purine/pyrimidine) triplexes. The triplexes can also be formed in nuclei. However, for all the sequences tested, we were unable to detect any triple helix formation in vivo in intact cells by DMS footprinting. Our results show that neither (i) chromatinization of the DNA target, (ii) intracellular K+concentration nor (iii) cytoplasmic versus nuclear separation of the TFO and DNA target are responsible for the intracellular arrest of triplex formation. We suggest the existence of a cellular mechanism, based on a compartmentalization of TFOs and/or TFO trapping, which separates oligonucleotides from the DNA target. Further work is needed to find oligonucleotide derivatives and means for their delivery to overcome the problem of triplex formation inside cells.